ANALISIS USABILITY MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE PADA WEBSITE MEDISOL - Jessica Chanarly; Mohammad Fajar; Arianti (STMIK KHARISMA Makassar, 2022)
The aim of this study is to analyze the usability of the Medisol website using the User Experience Questionnaire (UEQ) method so that it can be further developed according to user needs in the future. This analysis was carried out using four variables from the User Experience Questionnaire method: Usefulness, Ease of Use, Ease of Learn, and User Satisfaction. Usability measurement is obtained from the percentage of feasibility based on a questionnaire distributed to users who access the Medisol website with 30 respondents. In addition, the Likert scale was used to facilitate filling out the questionnaire and processing of the results by researchers. Based on calculations on the aspects covered by the User Experience Questionnaire (UEQ) method, the results obtained are 86% on the Usefulness aspect, 86% on the Ease of Use aspect, 89.67% on the Ease of Learn aspect, and 84.48% on the User Satisfaction aspect. It is said that the Medisol website perfectly fulfills these aspects. And from the usability calculation results obtained, namely 86.13%, it can be concluded that the percentage level of the Medisol website eligibility can be categorized as very feasible.